2020
DOI: 10.3389/fphys.2020.615351
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in Calcium Homeostasis Promotes Skeletal Muscle Atrophy: Lessons From Ventilator-Induced Diaphragm Wasting

Abstract: Mechanical ventilation (MV) is often a life-saving intervention for patients in respiratory failure. Unfortunately, a common and undesired consequence of prolonged MV is the development of diaphragmatic atrophy and contractile dysfunction. This MV-induced diaphragmatic weakness is commonly labeled “ventilator-induced diaphragm dysfunction” (VIDD). VIDD is an important clinical problem because diaphragmatic weakness is a major risk factor for the failure to wean patients from MV; this inability to remove patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…Specifically, oxidative stress can elevate proteolysis in three independent ways. First, oxidative stress often results in increased cytosolic free calcium, and elevated cytosolic calcium can activate both calpains and caspase-3 [ 19 , 20 , 37 , 38 ]. Second, redox disturbances can stimulate several transcriptional activators that promote expression of genes involved in proteolysis (i.e., atrogenes) [ 39 , 40 ].…”
Section: Signaling Links Between Mitochondrial Dysfunction and Skeletal Muscle Wastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, oxidative stress can elevate proteolysis in three independent ways. First, oxidative stress often results in increased cytosolic free calcium, and elevated cytosolic calcium can activate both calpains and caspase-3 [ 19 , 20 , 37 , 38 ]. Second, redox disturbances can stimulate several transcriptional activators that promote expression of genes involved in proteolysis (i.e., atrogenes) [ 39 , 40 ].…”
Section: Signaling Links Between Mitochondrial Dysfunction and Skeletal Muscle Wastingmentioning
confidence: 99%
“…Mitochondrial calcium overload is often associated with increased mitochondrial ROS production and activation of the mitochondrial permeability transition pore [ 82 , 83 , 84 , 85 ]. Therefore, mitochondrial calcium overload is a proposed mechanism for explaining the mitochondrial dysfunction associated with prolonged muscle inactivity (reviewed in [ 38 ]).…”
Section: Mitochondrial Dysfunction and Skeletal Muscle Atrophymentioning
confidence: 99%
“…The amplitude and CT parameters of contractions are related to the regulation of the contractile apparatus, and thus to calcium [Berridge et al, 2003]. Although the mechanism behind changes in the twitch durations associated with atrophy is unknown, it has been suggested that atrophy may be involved in the altering of Ca 2+ signaling [Hyatt and Powers, 2020] or the handling of Ca 2+ by Ca 2+ binding proteins [Fitts et al, 1986; Weiss et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, moderate influx of Ca 2+ into the organelle is important in facilitating oxidative phosphorylation in muscle mitochondria [143][144][145]. However, the increased levels of mitochondrial ROS that occur with chronic disuse lead to the oxidation of the RyR1, which promotes excessive Ca 2+ leak into the cytosol as well as an overload of Ca 2+ that is taken up by mitochondria [146]. As a result, the elevated levels of Ca 2+ lead to mitochondrial swelling and subsequent release of pro-apoptotic factors, as well as the activation of various proteolytic and apoptotic factors within the cytosol that collectively promote muscle atrophy via DNA fragmentation and myonuclear decay [33].…”
Section: Mitochondrial Ros Production and Ca 2+ Homeostaismentioning
confidence: 99%